The Effect of Fermentation Time on The Quality of Mocaf (Modified Cassava Flour) with Raw Material Bokor Genotype Cassava - Prastiwi, Erfa Kurnia; Fatoni, Rois; Fathoni, Ahmad; Setiarto, R. Haryo Bimo; Damayanti, Ema (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Cassava genotype Bokor has a fairly high content of beta carotene, which is beneficial for health and can also support the development of the functional food industry. MOCAF (Modified Cassava Flour) is a product made from cassava flour which is processed by modifying cassava cells through fermentation. This study aims to analyze the effect of long fermentation time on the characteristics of MOCAF from beta-carotene-rich cassava genotype Bokor. In this study, three variations of fermentation time were used, namely 15 hours, 24 hours and 40 hours. The research results showed that the time of fermentation affected the physicochemical properties of MOCAF. NIR analysis showed that the fermentation time affected the chemical composition of MOCAF. At 40 hours (last time of fermentation), there was a decrease in fat content with a value of 1.59% and an increase in water, protein and fibre content with a value of 13.71%, 3.94% and 2.28%, respectively. Proximate analysis showed that there was an effect of the length of fermentation time on the MOCAF content, namely at 40 hours, there was an increase in water content with a value of 10.10%, a decrease in dry matter, ash, protein, fat, fibre with a value of 89.90%, 0.60%, 0.78% respectively, 0.45%, and 1.29%. Scanning Electron Microscope (SEM) analysis shows the effect of fermentation time on the morphological properties of MOCAF starch granules. The longer the fermentation time, the more perforated or damaged the surface of the starch granules. Keywords:  Fermentation time, MOCAF flour, NIR (Near Infrared), Proximate, SEM (Scanning Electron Microscope)